Dearomatization–Rearomatization Strategy for Palladium-Catalyzed C–N Cross-Coupling Reactions - Lang, Yatao; Li, Chao-Jun; Zeng, Huiying (Synlett, 2020)
Substituted aromatic compounds play important roles in materials, biological agents, dyes, etc. Thus, the synthesis of substituted aromatic compounds has been a hot topic throughout the history of organic chemistry. Traditionally, the Friedel–Crafts reaction was a powerful tool for synthesizing substituted aromatic compounds. In recent decades, metal-catalyzed cross-coupling reactions were well developed via carbon–heteroatom bond cleavage, however, having difficulties towards some strong bonds, such as C(Ar)–OH. To overcome such challenges, newer strategies are needed. In this review, we summarize the recent efforts in the development of dearomatization–rearomatization strategy for cross-coupling reactions via C(Ar)–O bond cleavage.1 Introduction2 Dearomatization–Rearomatization Strategy for Cross-Coupling of Phenols3 Dearomatization–Rearomatization Strategy for Cross-Coupling of Biphenols4 Dearomatization–Rearomatization Strategy for Cross-Coupling of Diphenyl Ethers5 Dearomatization–Rearomatization Strategy for Cross-Coupling of Indoles6 Summary
Keywords: dearomatization–rearomatization strategy; C(Ar)–O bond cleavage; cross-coupling reaction; transition-metal catalyzed; aromatic compounds